MEASURING HOSPITAL EFFICIENCY DURING COVID-19 PANDEMIC IN INDONESIA - Anjani, Yani; Qadri, Resi Ariyasa; Fitrijanti, Tetet (JRAK, 2024)
By addressing indicators of inefficiency at the initial of the COVID-19 pandemic, hospitals can immediately respond through resources. This research aims at assessing the efficiency of both government and commercial hospitals in Indonesia during the pandemic. Accounting data was collected from documentation of financial statements. The data was analyzed by using the data envelopment analysis technique and Tobit regression. The research showed that over three years of the pandemic, the hospital's efficiency rate decreased successively by 100%, 86%, and 76%. However, the optimization of hospital efficiency can be significantly improved by revenue factors, specifically the quantifiable quantity of income generated. This highlighted the need to increase revenue to ensure the provision of high-quality services to the general population. It is hoped that this research will shed light on the challenges faced by hospitals during these difficult times and provide insights for future improvements.